2016
DOI: 10.1371/journal.pone.0161469
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Structural Models to Assess Delays in Second-Line HIV Treatment Initiation in South Africa

Abstract: BackgroundSouth African HIV treatment guidelines call for patients who fail first-line antiretroviral therapy (ART) to be switched to second-line ART, yet logistical issues, clinician decisions and patient preferences make delay in switching to second-line likely. We explore the impact of delaying second-line ART after first-line treatment failure on rates of death and virologic failure.MethodsWe include patients with documented virologic failure on first-line ART from an observational cohort of 9 South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
4
36
1
1
Order By: Relevance
“…Previous reports from sub-Saharan African settings have consistently shown low and delayed switching from first-to second-line ART (even when VL-monitoring is present), which have been linked to poorer treatment outcomes, increased mortality and the risk of the development and transmission of resistance [8,32,[60][61][62][63]. In our sites, 80% of first-line treatment failures were switched to second-line, an encouraging figure that is higher than in similar programmes (43%, Swaziland; 33%, Mozambique [50,64] three-test failure algorithm or the non-capture of VL-tests in the electronic database.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from sub-Saharan African settings have consistently shown low and delayed switching from first-to second-line ART (even when VL-monitoring is present), which have been linked to poorer treatment outcomes, increased mortality and the risk of the development and transmission of resistance [8,32,[60][61][62][63]. In our sites, 80% of first-line treatment failures were switched to second-line, an encouraging figure that is higher than in similar programmes (43%, Swaziland; 33%, Mozambique [50,64] three-test failure algorithm or the non-capture of VL-tests in the electronic database.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, Johnston and colleagues had previously shown for a large multicentre cohort in Johannesburg a high reluctance among healthcare providers to switch patients to second-line ART - even after confirmed treatment failure [ 11 ]. Rohr and colleagues reported from a large cohort of nine clinics in South Africa that only about half of the patients failing first-line therapy were switched to second line within 12 months after the diagnosis of treatment failure [ 26 ]. These South African studies were conducted in large, well-established HIV care centres.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are in line with earlier reports from South Africa [ 12 , 27 ]. In the cohort study of Rohr et al, after switch to second line, 14% experienced confirmed virologic failure on second line, 42% remained in care with regular VL monitoring, 12% remained in care but had missed VL monitoring visits, 30% stopped attending the clinic and 2% died [ 26 ]. In a randomized controlled trial conducted in three West African countries, 65% achieved viral suppression (<50 copies/mL) after switch to second line [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, on the ground, switch delays in South Africa are nearly twice that—a median of 3.4 months—with 37% of patients with first-line ART failure in South Africa failing to switch. 4 …”
Section: The Causes and Costs Of Late Or Missed Second-line Switchmentioning
confidence: 99%